2007
DOI: 10.1080/08838150701304969
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Socialization Messages on Television Programs Most Popular Among Teens

Abstract: This paper examines the portrayal of sexual messages in the top 20 most popular television programs among teenagers in the United States. It compares findings from the 20012002 and 20042005 seasons. Results show that these programs contained a large number of sexual messages, though their frequency decreased over time. Most messages about sex were in the form of conversations. About 1 in 2 shows included portrayals of sexual behaviors, mostly precursory behaviors. Sexual risk and responsibility concerns were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 28 publications
1
20
0
3
Order By: Relevance
“…In line with other content analyses focusing on program genres (e.g., Aubrey, 2004;Eyal, Kunkel, Biely, & Finnerty, 2007;Farrar et al, 2003;Wallis, 2011), the coding was conducted at the level of scenes. Scenes were defined as exchanges that occurred in a single setting without interruption by time or changes in location (Van Mierlo, 2007).…”
Section: Units Of Analysis: Scenesmentioning
confidence: 99%
“…In line with other content analyses focusing on program genres (e.g., Aubrey, 2004;Eyal, Kunkel, Biely, & Finnerty, 2007;Farrar et al, 2003;Wallis, 2011), the coding was conducted at the level of scenes. Scenes were defined as exchanges that occurred in a single setting without interruption by time or changes in location (Van Mierlo, 2007).…”
Section: Units Of Analysis: Scenesmentioning
confidence: 99%
“…Much attention has been focused on its potentially harmful ramifications for the young, particularly violence (see Huesmann and Taylor, 2006;Anderson, Gentile, and Buckley, 2007 for reviews) and portrayals of sexual behavior (Eyal, Kunkel, Biely, & Finnerty, 2007;Zhang, Miller, & Harrison, 2008;Brown et al, 2006;Chandra et al, 2008;Collins et al, 2004). An emerging literature has shown that fiction can effect learning and real world beliefs for adult audiences as well.…”
Section: Fictional Media and Real World Beliefsmentioning
confidence: 99%
“…In general, a liberal stance is taken on the topic of sexuality, as is illustrated by the frequent examples of casual sex (cf. Eyal et al 2007). Moreover, this ideal fictional world is ruled by heteronormativity, and fails to address the topics of contraception and STDs, probably due to the influences of advertisers.…”
Section: Discussionmentioning
confidence: 93%